2022
DOI: 10.1007/s10151-022-02626-9
|View full text |Cite
|
Sign up to set email alerts
|

Robotic oncologic colorectal surgery with a new robotic platform (CMR Versius): hope or hype? A preliminary experience from a full-robotic case-series

Abstract: Background The present case-series describes the first full-robotic colorectal resections performed with the new CMR Versius platform (Cambridge Medical Robotics Surgical, 1 Evolution Business Park, Cambridge, United Kingdom) by an experienced robotic surgeon. Methods In a period between July 2020 and December 2020, patients aged 18 years or older, who were diagnosed with colorectal cancer and were fit for minimally invasive surgery, underwent robotic colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The reported cases belonged to several specialties: hepatopancreatobiliary surgery [13, 37-39,50-55,78,79,87-97,100-103] (Tables S1 and S2), colorectal surgery [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][88][89][90][91][93][94][95][96][97][98][104][105][106][107][108][109][110][111] (Tables S1 and S3), abdominal wall surgery [11,12,[47][48][49][87][88][89][90][93]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported cases belonged to several specialties: hepatopancreatobiliary surgery [13, 37-39,50-55,78,79,87-97,100-103] (Tables S1 and S2), colorectal surgery [56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][88][89][90][91][93][94][95][96][97][98][104][105][106][107][108][109][110][111] (Tables S1 and S3), abdominal wall surgery [11,12,[47][48][49][87][88][89][90][93]…”
Section: Resultsmentioning
confidence: 99%
“…Forty-five (43.7%) authors reported the surgical background of the operating surgeon and his previous experience [26,31,33,45,[47][48][49][50][51][52][53][54][55][56][57][58][59]62,64,67,69,76,77,79,[83][84][85][86][87][88][89][90][91][92]94,96,99,[102][103][104][105][106][108][109][110]. A structured training process of the surgical team on the adopted system was reported by 28 (27.2%) authors [26,40,[47][48][49]…”
Section: Trainingmentioning
confidence: 99%
“…Versius is a novel robot that slightly differs from the standard of other robotic systems, leading to extra precautionary measures to be taken to decrease the fighting and clashing of instruments [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the positions of bedside units (BSUs) were found to limit the assistant surgeon from having a proper position, which led to uncomfortable adjustments when performing high-risk tasks. Another point found within this study is that the platform’s dexterity was not optimal due to missing certain anatomical structures while adjusting the directions of the instruments [ 7 ]. However, the flexibility of the bedside units provided increased flexibility in port placement, which has reduced the learning curve, making the initial experience with such a system preferable [ 8 – 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…We wish to stress the importance of detecting the avascular plane between Told and Gerota fascia, just after the opening of the Jonnesco fold and the incision of the Monk line. 3 IMA is dissected free dividing sigmoid arteries (usually 3) at their origin. Similarly, sigmoidal veins are dived at their confluence into IMV.…”
mentioning
confidence: 99%